A two-center randomized trial of an additional early dose of measles vaccine: effects on mortality and measles antibody levels - Fisker, Ane B.; Nebie, Eric; Schoeps, Anja; Martins, Cesario; Rodrigues, Amabelia; Zakane, Alphonse; Kagone, Moubassira; Byberg, Stine; Thysen, Sanne M.; Tiendrebeogo, Justin; Coulibaly, Boubacar; Sankoh, Osman; et al. (Clinical infectious diseases, 2018)
In a randomized trial of an extra dose of early measles vaccine in Burkina Faso and Guinea-Bissau, we found no effect on mortality. Children had low antibody le